1996
DOI: 10.1021/ja960056m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Proton-Coupled Electron Transfer for Quinone (QB) Reduction in Reaction Centers of Rb. Sphaeroides

Abstract: The mechanism of the proton-coupled electron transfer reaction, Q A -Q B -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
222
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(242 citation statements)
references
References 66 publications
15
222
0
Order By: Relevance
“…A detailed procedure for reconstitution of the Q A binding site with naphthoquinone and Q B binding site with ubiquinone has been presented (11). The occupancy of the Q A and Q B sites after reconstitution were determined from the amplitudes of transients associated with charge recombination, k AD (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed procedure for reconstitution of the Q A binding site with naphthoquinone and Q B binding site with ubiquinone has been presented (11). The occupancy of the Q A and Q B sites after reconstitution were determined from the amplitudes of transients associated with charge recombination, k AD (18).…”
Section: Methodsmentioning
confidence: 99%
“…If k C Ͼ k ET , the reaction is rate-limited by electron transfer. To determine which of these two cases prevails, a driving force assay was used (11). In this assay, quinones with different redox potentials (i.e., driving force) are substituted for Q A , thereby changing the driving force for electron transfer and, thus, the intrinsic rate constant, k ET .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fluoride (pK a ϭ 3.16) and phosphate (pK a ϭ 2.15) were unable to fully restore the rate, or even to attain the same level as azide (pK a ϭ 4.72). However, this is readily accounted for if we allow for the anion (A Ϫ ) to interact at the same site as the acid (57,58) and is largely unaffected by conditions and mutations that induce significant electrostatic changes in the acid cluster of the Q B domain (28,30). We therefore take the wild-type value of k ET ϭ 10 6 s Ϫ1 .…”
Section: L210mentioning
confidence: 99%
“…A proton-activated electron-transfer mechanism has been proposed which suggests the fast protonation of Q B , prior to the slower rate-limiting electron-transfer (6,8,13). However, in chromatophores from R. sphaeroides, it was shown that, at the first flash, Q B can be protonated with a pK of ∼6.8 (14), suggesting that there might be no fundamental differences between the first and second electron-transfer processes.…”
mentioning
confidence: 99%